FLASHCARD MEDIA: THE MEDIA FOR DEVELOPING STUDENTS UNDERSTANDING FOR ENGLISH VOCABULARY AT ELEMENTARY SCHOOL - Herlina Herlina; Raden Rahmi Dewi (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The purpose of this study was to analyze to develop in understanding English vocabulary by using flashcard media in students elementary school. This research was conducted at primary students in boarding school. The subjects were students of the third class with fourtee students. The research method was classroom action research using by model of Kemmis and Mc Taggart with four stages which including planning, action, observation, and reflection. Techniques of analysis the data collection through the results of monitoring action, analysis of learning activities, field notes and evaluative tests, as well as data collection by using documentation/photos taken during the learning process. Results obtained the understanding of vocabulary in the first cycle was 52.5%, and the second cycle was 80.0%. The average percentage of data monitoring the first cycle was 77.5% and the second cycle was 96.2%. Therefore learning by using flashcard media can improve their understanding of English vocabulary. The implication of this research is through flashcard media in learning English can motivated to students to improve the understanding of vocabulary in third grade students of elementary schooll in boarding school.